2020
DOI: 10.1089/cyber.2019.0370
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying and Children and Young People's Mental Health: A Systematic Map of Systematic Reviews

Abstract: Cyberbullying is associated with considerable negative mental and psychosocial consequences in children and young people, making it a serious public health concern. To review the highest level of available evidence, a systematic mapping review was conducted to identify systematic reviews that investigated the relationship between cyberbullying and mental and psychological outcomes in young people. Topic-relevant bibliographic databases and online resources were searched to identify reviews published since 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(119 citation statements)
references
References 59 publications
6
108
0
5
Order By: Relevance
“…Although there is growing evidence of the adverse effects of cybervictimization on adolescent adaptation (Aricak and Ozbay, 2016;Palermiti et al, 2017;Kwan et al, 2020), little research has examined its mediating and moderating mechanisms. To address this gap, this study investigated whether depression mediates the relationship between cybervictimization and adolescent's IA, and whether this mediating effect is moderated by PPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is growing evidence of the adverse effects of cybervictimization on adolescent adaptation (Aricak and Ozbay, 2016;Palermiti et al, 2017;Kwan et al, 2020), little research has examined its mediating and moderating mechanisms. To address this gap, this study investigated whether depression mediates the relationship between cybervictimization and adolescent's IA, and whether this mediating effect is moderated by PPA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that adolescents who suffer from cybervictimization often exhibited a series of psychological problems, such as anxiety, loneliness, low self-esteem, and depression (Guo, 2016). However, among the many adverse consequences of cybervictimization, depression seems to be one of the most common and important (Kowalski et al, 2014;Kwan et al, 2020). Both previous cross-sectional and longitudinal studies can provide evidences that cybervictimization is an important risk factor for depressive symptoms (Landoll et al, 2015;Calvete et al, 2016;Chu et al, 2018), which means that adolescents are more likely to develop depressive symptoms after suffering from cybervictimization.…”
Section: The Mediating Role Of Depressionmentioning
confidence: 99%
“…While certainly prevalent and relevant for MH, these forms of CMC are highly specific concerning message style, interaction context, and user characteristics. Moreover, they have been extensively reviewed elsewhere and thus lie outside the scope of this review (Chen et al, 2017;Kosenko et al, 2017;Kowalski et al, 2014;Kwan et al, 2020;Tokunaga, 2010). c. Furthermore, and in line with our focus on CMC, we excluded reviews on games.…”
Section: Appendix Ii: Detailed Eligibility Criteria and Review Exclusmentioning
confidence: 99%
“…Examples of cyberbullying victimization include repeatedly sending harassing or offensive messages to victims and publicly posting harmful information and content on the Internet (4,5). Ample research has documented that there is a high prevalence of cyberbullying victimization among Chinese adolescents with rates that are increasing annually (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%